Hypophosphatasia: A Novel Mutation Associated with an Atypical Newborn Presentation - Roger Esmel-Vilomara; Susana Hernández; Ariadna Campos-Martorel; Eva González-Roca; Diego Yeste; Félix Castillo (JCRPE, 2020)

(untitled)
Hypophosphatasia, a rare genetic disease affecting bone metabolism, is characterized by decreased activity of tissue non-specific alkaline phosphatase (TNAP). The gene encoding TNAP (ALPL) has considerable allelic heterogeneity, which could explain different degrees of enzyme activity resulting in a wide clinical variability. We report the case of a preterm newborn in whom a corneal opacity was detected at birth. Blood tests performed to investigate this finding showed low alkaline phosphatase concentrations. The corneal opacity disappeared within a week but alkaline phosphatase remained persistently low. With persistently decreased levels of alkaline phosphatase, upon suspicion of hypophosphatasia, plain radiography detected changes suggestive of rickets. Sequencing of the ALPL gene revealed a heterozygous variant that has not been described in the literature to date. Our patient’s condition may be an atypical neonatal form of the syndrome, with a mild phenotype, very different from the classic neonatal form, which can lead to severe skeletal disease and respiratory failure. However, it could also be an early diagnosis of the childhood form, which is associated with a better prognosis.